PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA SISWA KELAS X IPA - Nurdiana, Aty (LPPM STKIP PGRI Bandar Lampung, 2019)
Abstract: The problems discussed in the study relate to the ability to solve mathematical problems in the X graders of science in the even semester of SMA Negeri 3 Bandar Lampung, which are still low. Based on this, this study aims to determine the effect of the Discovery Learning model on the ability of mathematical problem solving in class X science students of Even Semester SMA Negeri 3 Bandar Lampung in the Academic Year 2017/2018. The method used in this research is the experimental method. The population in this study were all students of class X IPA in the even semester of SMA Negeri 3 Bandar Lampung in the academic year 2017/2018, which were spread in 6 classes with a total of 206 students. From the population, two classes were taken as the research sample, namely class X IPA 2, amounting to 30 students as the control class and X IPA 4, amounting to 35 students as the experimental class. The sampling technique used is the Cluster Random Sampling technique. Measurement of variables using a test in the form of a description of 5 questions that were first tested for validity and reliability. Data analysis uses simple statistical analysis with the t-test formula. Based on the results of hypothesis testing, obtained thit = 5.24 and from the distribution table at a significant level of 5% with tdaf = t (1-1/2Î±) = 1.67 so that it is known thit> tdaf or can be written 5.24> 1.67 . Thus it can be concluded